Incorporation and taxation : theory and firm-level evidence - Peter Egger; Christian Keuschnigg; Hannes Winner (Center for Economic Studies and ifo Institute (CESifo), 2009)
This paper provides a theory and firm-level evidence on the incorporation decision of entrepreneurs in a model of taxes and corporate governance. The theory explains how the incorporation decision of entrepreneurs is driven by taxation (corporate and personal income taxes), corporate transparency, access to external capital and limited liability. We estimate features of this model using a large cross-section of more than 540, 000 firms in European manufacturing. We find that higher personal income tax rates favor incorporation while higher corporate tax rates reduce the probability to incorporate. These findings are robust to the inclusion of other economic and institutional determinants of external financing and choice of organizational form.
Keywords: H25; H73; F23; C21; 330; incorporation; governance; taxes; discrete choice models; Unternehmen; Rechtsform; Umwandlung; Unternehmensbesteuerung; Einkommensteuer; Corporate Governance; EU-Staaten